Citizen-Scholars: Social Media and the Changing Nature of Scholarship - Amy L. Chapman; Christine Greenhow (Publications, 2019)
Research is rarely created for private use; researchers publish their work so that others can read and use it, to advance the collective understanding of a field and impact people’s lives. Yet traditional approaches to scholarship, which emphasize publication in subscription-based rather than open access journals, inhibit not only the dissemination of research but also its usefulness, particularly outside of academia. Across all fields, scholars, educators, and members of the public benefit from scholarship which is easily accessible. Open science and public, social scholarship can break down these barriers to accessibility and utility. In this age which calls for a more informed citizenry, the use of social media to share and promote discussion of research could change not only the nature of scholarly communication but also the nature of scholarship and scholars’ roles. In this conceptual article, we argue that practicing public, social scholarship and increasing the use of social media to promote scholarship are the civic responsibility of citizen-scholars, so that research becomes more widely accessible, shareable, and usable in the public sphere.